Open Spaces and Transformations in the Territory of the Encosta Norte Housing Complex, East Side of São Paulo - Pinheiro , Rita de Cássia Nogueira; Paula, Franklin Roberto Ferreira de; Imbronito, Maria Isabel (National Journal of City Management, 2022)
This article consists of an analysis of open spaces network in the Encosta Norte Housing Complex, located in the city of São Paulo. The complex accommodates a series of open areas in its extensive area that can be grouped into three categories: programmed spaces, spaces of spontaneous use and spaces of potentiality. The first group consists of squares conceived in the original CDHU project and which contain equipment and furniture for permanence, leisure and physical exercise. The second group is the result of the transformation processes that the area has undergone since the installation of the complex and whose uses have been adapted gradually. Potential areas are empty awaiting definition of form and use. This article aims to understand how the network of open spaces is constituted and consolidated from the use that residents make of it. To this end, the methodology applied uses technical visits to the site, interviews with technicians from the CDHU, in addition to the analysis of documents such as maps, projects and literature review. As a result, a fragmented territory was found, with free spaces included in the different categories listed, and which, at times, distanced itself from the planned condition during the idealization of the set. It is possible to understand that this network of open spaces in the Encosta Norte Housing Complex is diversified and made more flexible depending on how residents use each of these spaces: sometimes as a permanence, sometimes as a crossing, sometimes as leisure, sometimes as a latency void.